2021
DOI: 10.3390/jcs5030066
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Modifications of Activated Carbon Materials on the Capacitive Performance: Surface, Microstructure, and Wettability

Abstract: In this review, the efforts done by different research groups to enhance the performance of the electric double-layer capacitors (EDLCs), regarding the effect of the modification of activated carbon structures on the electrochemical properties, are summarized. Activated carbon materials with various porous textures, surface chemistry, and microstructure have been synthesized using several different techniques by different researchers. Micro-, meso-, and macroporous textures can be obtained through the activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 107 publications
0
17
0
Order By: Relevance
“…The prepared working electrode was then soaked in the electrolyte solution at room temperature for over 12 h. The electrochemical experiments were carried out by a three-electrode system. The three-electrode configuration is useful in the investigation of the chemistry of the active electrode surface as well as the redox behavior of the active electrode material . Two different aqueous electrolytes were used in the electrochemical experiments.…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
“…The prepared working electrode was then soaked in the electrolyte solution at room temperature for over 12 h. The electrochemical experiments were carried out by a three-electrode system. The three-electrode configuration is useful in the investigation of the chemistry of the active electrode surface as well as the redox behavior of the active electrode material . Two different aqueous electrolytes were used in the electrochemical experiments.…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
“…The peak current decreased after the modification of the GCE with APC with an increase in the Δ E , which may be attributed to the low conductivity of the latter. 59 While coating the APC with ZnO NPs, peak currents were greatly increased (around 76% for I pa and 63% for I pc as compared to GCE bare) and electrode performance was improved, which can be explained by the enhanced conductivity issued by ZnO NPs due to their intrinsic electrocatalytic properties. This suggested that the metal oxide had facilitated electron transfer and enhanced the electroactive surface area of the electrode.…”
Section: Resultsmentioning
confidence: 98%
“…The presence of micro-and mesopore delays the charge transfer, which limits accessibility to the electrode surface. 59 Once ZnO was added to the carbon support, the semicircle had strongly diminished and revealed an R ct value of 23.09 ohm cm 2 because the conductivity of the electrode increased due to ZnO NPs, which facilitated electron transfer between the electrochemical probe redox and the electrode surface. Moreover, the presence of Pd NPs in the Pd/ZnO/APC nanocomposite led to further suppression in the semicircle with a low R ct of 14.56 ohm cm 2 .…”
Section: Electrochemical Characterization Of the Materialsmentioning
confidence: 99%
“…As expected, the functionalization of graphite felt with Co 3 O 4 led to a decrease in the hydrophobicity, corresponding to a reduction of the contact angle to 116 ± 0.6° from a value of 139 ± 0.1° for plain GF (Figure 2a). This improvement in the electrode wettability could result from the oxygen atoms introduced by Co 3 O 4 that could alter the electrostatic field at the surface of graphite felt and facilitate interaction between the electrode material and water molecules 45,28 . The electrodeposition of PANI further decreased the surface hydrophobicity, with PANI-Co 3 O 4 -GF reaching a contact angle of 97 ± 0.9.…”
Section: Physicochemical Characterizations Of the Anodes Developedmentioning
confidence: 99%